POTENTIAL PRODUCTION OF NIRA ENAU (ARENGA PINNATA MERR) AT BUKIK BARISAN DISTRICTS, LIMAPULUH KOTA REGENCY - Trisia Wulantika (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
Nira is a fluid that comes out of the male flower that is obtained by means of tapped and has a sweetness. Nira Enau can be used for the manufacture of brown sugar, sugar ant palm, Tuak and bioethanol making raw materials. Bukik Barisan Subdistrict is one of the sub-districts of Kab.Limapuluh Kota with the area of Enau is large enough to be 95 Ha. This study has been implemented in January-April 2018 at 4 Kenagarian in the Kec. Bukik Barisan with purposive sampling method and data analyzed descriptively using simple statistical methods. Based on the research that has been carried out results, Kenagarian Banjar Lawas has an average production of nira per day higher than 3 other Kenagarian is 8.29 Liter/day, while for the measurement of sugar content, the average accession Enau in the Kenagarian Koto Tangah has a higher sugar level than other Kenagarian, namely 15.75 Brix. Enau plant in Bukik Barisan Sub District is very potential to be developed because it has a high production potential per day that is quite high along with the sugar content which is also higher.